Lithium supplement material and preparation method thereof, positive pole piece and lithium ion battery

By using transition metal lithium-containing lithium-enhancing materials coated with carbon cladding in lithium-ion batteries, the problem of low charging and discharging efficiency for the first time in lithium-ion batteries is solved, and the effect of effectively decomposing and releasing lithium ions at a lower voltage is achieved, and the energy density of the battery is improved.

CN119695153APending Publication Date: 2025-03-25HUIZHOU TOPBAND ELECTRICAL TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411716470.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Existing lithium-ion batteries are low in efficiency during the first charging and discharging, and the high charging voltage platform leads to instability of the positive electrode material, oxidation and decomposition of the electrolyte, and local overcharging of the negative electrode, making it difficult to effectively utilize lithium supplement agents.

Method used

A lithium supplement material is used, which includes a core and a carbon cladding layer covering the surface of the core part, the core contains transition metal elements and lithium-containing compounds, and the carbon cladding layer has holes. The material is prepared by mixing and reacting molten metal lithium with a transition metal compound composite material under an inert atmosphere.

Benefits of technology

The decomposition voltage of lithium supplement material is reduced, so that it can effectively decompose and release lithium ions at a lower voltage, optimize the formation of SEI film, and improve the first charge and discharge efficiency and mass energy density of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695153A_ABST
    Figure CN119695153A_ABST
Patent Text Reader

Abstract

The invention provides a lithium supplement material and a preparation method thereof, a positive pole piece and a lithium ion battery, and belongs to the technical field of batteries. The lithium supplementing material comprises an inner core and a carbon coating layer coating at least part of the surface of the inner core, the inner core comprises a lithium supplementing agent, and the lithium supplementing agent comprises a transition metal element and a lithium-containing compound; and the carbon coating layer is provided with holes. The lithium supplementing material disclosed by the invention has relatively low decomposition voltage, lithium ions of the positive electrode material can be separated and participate in formation of an SEI (Solid Electrolyte Interface) film during first-time charging, and the consumption of the lithium ions of the positive electrode material in the process of participating in formation of the SEI film is reduced, so that the first-time charging and discharging efficiency of the battery is improved; in addition, the positive electrode can provide more lithium ions to participate in electrochemical reaction, so that the mass energy density of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a lithium supplement material and a preparation method thereof, a positive electrode sheet and a lithium ion battery. Background Art

[0002] In order to improve the energy density of lithium-ion batteries, adding lithium supplements is a very promising development direction, among which positive electrode lithium supplementation has the characteristics of strong operability and easy industrialization.

[0003] Currently, the positive electrode lithium supplements that are widely studied in the industry include lithium-containing metal oxides. The charging voltage platform of this type of lithium supplement is very high. When charging for the first time, it needs to be charged to a high voltage so that the capacity of the lithium supplement can be better utilized. However, charging to a high voltage state will bring many problems to lithium-ion batteries: For example, the positive electrode material is unstable and prone to decomposition; the electrolyte is prone to oxidation and decomposition under high voltage; the negative electrode is prone to local overcharging and lithium precipitation. Therefore, this type of lithium supplement is difficult to play a role in the SEI formation stage.

[0004] Although the lithium supplement agent is compounded with the catalyst in the related art, the reduction of the decomposition voltage of the lithium supplement agent is not obvious, resulting in the initial charge and discharge efficiency of the lithium-ion battery. Summary of the invention

[0005] In view of the above problems, the present invention provides a lithium supplement material and a preparation method thereof, a positive electrode plate and a lithium ion battery, aiming to improve the initial charge and discharge efficiency of the lithium ion battery.

[0006] In a first aspect, the present invention provides a lithium supplement material, comprising a core and a carbon coating layer covering at least a portion of the surface of the core; the core comprises a lithium supplement agent, the lithium supplement agent comprises a transition metal element and a lithium-containing compound; the carbon coating layer has pores.

[0007] In some embodiments, the molar ratio of the transition metal element to the lithium-containing compound is 1:(1.3-2).

[0008] In some embodiments, the transition metal element includes at least one of iron, nickel, cobalt, manganese, vanadium, and chromium.

[0009] In some embodiments, the lithium-containing compound includes at least one of a lithium-containing oxide, a lithium-containing fluoride, and a lithium-containing sulfide.

[0010] In some embodiments, the pores have a pore size of 10 nm-200 nm.

[0011] In some embodiments, the lithium supplement material satisfies at least one of the following conditions:

[0012] The particle size D of the lithium supplement material V500.5μm-5μm;

[0013] The thickness of the carbon coating layer is 1nm-50nm;

[0014] The mass ratio of the core to the carbon coating layer is 100:(0.5-3).

[0015] In a second aspect, the present invention provides a method for preparing a lithium supplement material, comprising:

[0016] A transition metal compound composite material is provided, the transition metal compound composite material comprises a transition metal compound and a carbon coating layer covering at least a portion of the surface of the transition metal compound, the carbon coating layer having pores;

[0017] Under an inert atmosphere, molten metal lithium is mixed with the transition metal compound composite material for reaction, and a lithium supplement material can be obtained after the reaction is completed.

[0018] In some embodiments, the “providing a transition metal compound composite material” comprises:

[0019] mixing a transition metal compound with an organic matter to obtain a mixture;

[0020] The mixture is carbonized under an inert atmosphere to obtain a transition metal compound composite material.

[0021] In some embodiments, the transition element of the transition metal compound includes at least one of iron, nickel, cobalt, manganese, vanadium, and chromium.

[0022] In some embodiments, the transition metal compound includes at least one of cobalt trioxide, cobalt trifluoride, ferroferric tetroxide, ferric trifluoride, and ferrous oxide fluoride.

[0023] In some embodiments, the organic matter includes at least one of starch, sucrose, glucose, and asphalt.

[0024] In some embodiments, the mass ratio of the transition metal compound to the organic matter is 1:(0.05-0.2).

[0025] In some embodiments, the “carbonizing the mixture to obtain a transition metal compound composite material” includes:

[0026] The mixture is heated from room temperature to a first carbonization temperature and kept at this temperature for 1 h to 3 h;

[0027] The mixture is heated from the first carbonization temperature to the second carbonization temperature and kept at this temperature for 4 h to 10 h.

[0028] In some embodiments, the first carbonization temperature is 300° C.-500° C.; and / or,

[0029] The second carbonization temperature is 600°C-1200°C; and / or,

[0030] The heating rate is 2°C / min-8°C / min.

[0031] In some embodiments, the step of “mixing molten lithium metal with the transition metal compound composite material for reaction” comprises:

[0032] Heating metallic lithium to 180° C.-190° C. to obtain molten metallic lithium;

[0033] Adding the transition metal compound composite material into the molten metal lithium and stirring evenly;

[0034] Then the temperature is raised to 200°C-240°C and the reaction is carried out at a constant temperature for 1h-5h.

[0035] In some embodiments, the stirring speed is 5 rpm-30 rpm, and the time is 20 min-40 min.

[0036] In a third aspect, the present invention provides a positive electrode plate, comprising any of the above-mentioned lithium-supplementing materials or a lithium-supplementing material prepared by any of the above-mentioned preparation methods.

[0037] In some embodiments, the lithium supplement material accounts for 0.5%-5.0% by mass in the positive electrode film layer.

[0038] In a fourth aspect, the present invention provides a lithium-ion battery comprising the above-mentioned positive electrode plate.

[0039] The lithium supplement material of the present invention comprises a core and a carbon coating layer, and the lithium supplement agent of the core comprises a transition metal element and a lithium-containing compound. On the one hand, the transition metal has a variable valence, and when compounded with a lithium-containing compound, it can promote the transfer of electrons in the reaction system, so that the lithium supplement agent can be decomposed and release lithium ions at a relatively low voltage. On the other hand, the carbon coating layer can significantly improve the conductivity of the lithium supplement material, and the good conductivity is conducive to the rapid transmission of charge, so that the lithium supplement agent can quickly respond to the change of voltage during the charging process and decompose at a relatively low voltage. Therefore, the lithium supplement material of the present invention has a relatively low decomposition voltage, and can be preferentially released before the lithium ions of the positive electrode material during the first charge, participate in the formation of the SEI film, reduce the consumption of the lithium ions of the positive electrode material in the process of forming the SEI film, thereby improving the first charge and discharge efficiency of the battery; in addition, the consumption of lithium ions of the positive electrode material is less, which means that under the same number of charge and discharge cycles, the positive electrode can provide more lithium ions to participate in the electrochemical reaction, thereby helping to improve the mass energy density of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 FIG. 1 is an XRD diagram of a lithium supplement material in one embodiment of the present invention. DETAILED DESCRIPTION

[0041] The following embodiments are only used to more clearly illustrate the technical solutions of the present invention and are therefore only used as examples and are not intended to limit the scope of protection of the present invention.

[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the specification and claims of the present invention and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0043] In the description of the embodiments of the present invention, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present invention, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0044] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0045] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0046] In the description of the embodiments of the present invention, the term "multiple" refers to more than two (including two), and similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces). The term "at least one" refers to one or more.

[0047] Lithium-containing metal oxide lithium supplements include Li6CoO4, Li2NiO2, Li5FeO4, Li2CuO2, Li2MoO3, etc. In lithium-containing metal oxides, the chemical bond between metal ions and oxygen ions is strong, and lithium-containing metal oxides usually have a relatively compact crystal structure, which results in a higher voltage required for lithium ions to escape from the oxide structure. Therefore, the charging voltage platform of lithium-containing metal oxide lithium supplements is very high. When charging for the first time, it is necessary to charge to a high voltage so that the capacity of the lithium supplement can be better utilized. Charging to a high voltage state will bring many problems to lithium-ion batteries: such as the positive electrode material is unstable and prone to decomposition; the electrolyte is prone to oxidative decomposition under high voltage; the negative electrode is prone to local overcharging and lithium precipitation. Therefore, this type of lithium supplement is difficult to play a role in the SEI formation stage.

[0048] Although the lithium supplement agent is compounded with the catalyst in the related art, the reduction of the decomposition voltage of the lithium supplement agent is not obvious, resulting in the initial charge and discharge efficiency of the lithium-ion battery.

[0049] Based on the above problems, the present invention provides a lithium supplement material, including a core and a carbon coating layer covering at least a portion of the surface of the core; the core includes a lithium supplement agent, the lithium supplement agent includes a transition metal element and a lithium-containing compound; the carbon coating layer has pores.

[0050] The carbon coating layer that covers at least part of the surface of the inner core means that the carbon coating layer can completely cover the inner core or partially cover the inner core. The carbon coating layer can improve the conductivity of the lithium supplement material. When compounded with the lithium supplement agent, it can improve the conductivity of the lithium supplement material. Good conductivity helps the rapid transmission of charge, so that the lithium-containing compound can respond to voltage changes more quickly during the charging process, thereby starting to decompose at a lower voltage. In addition, since some lithium-containing compounds such as lithium oxide, lithium fluoride, and lithium sulfide are very easy to react with water and carbon dioxide, the carbon coating layer can form a physical barrier to reduce the contact between the lithium-containing compound in the inner core and water and carbon dioxide in the air, thereby improving the stability of the lithium supplement agent.

[0051] The lithium supplement includes transition metal elements, which means that the lithium supplement may include transition metals, transition metal compounds, or both. Transition metal elements have catalytic effects. On the one hand, they have variable valences, which can promote the transfer of electrons in the reaction system when compounded with lithium-containing compounds, so that the lithium-containing compounds can undergo redox reactions at a lower voltage, thereby decomposing and releasing lithium ions; on the other hand, there are usually many active sites on the surface of transition metals, which can adsorb lithium-containing compounds or intermediates involved in the reaction, reducing the activation energy of the reaction. The reduction in activation energy means that the reaction is more likely to occur, which means that the decomposition of lithium-containing compounds can be achieved at a lower voltage. In addition, the transition metal itself also has good conductivity. After compounding with lithium-containing compounds, the conductivity of lithium-supplementing materials can be improved.

[0052] Therefore, the lithium supplement material of the present invention has a lower decomposition voltage, and can be released before the lithium ions of the positive electrode material during the first charge, participate in the formation of the SEI film, and reduce the consumption of the lithium ions of the positive electrode material in the process of forming the SEI film, thereby improving the first charge and discharge efficiency of the battery. In addition, the consumption of lithium ions of the positive electrode material is less, which means that under the same number of charge and discharge cycles, the positive electrode can provide more lithium ions to participate in the electrochemical reaction, thereby helping to improve the mass energy density of the battery.

[0053] According to some embodiments of the present application, the molar ratio of the transition metal element to the lithium-containing compound is 1:(1.3-2).

[0054] Exemplarily, the molar ratio of the transition metal element to the lithium-containing compound can be 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9 or 1:2. When the molar ratio of the transition metal element to the lithium-containing compound is between 1:(1.3-2), the lithium-containing compound can be decomposed at a lower voltage and the problem of metal dissolution caused by excessive doping can be reduced.

[0055] According to some embodiments of the present application, the transition metal element includes at least one of iron, nickel, cobalt, manganese, vanadium, and chromium.

[0056] Iron has a variety of oxidation states, such as +2 and +3, and can transfer and gain or lose electrons in chemical reactions. This redox property enables it to participate in related reactions in the lithium replenishment process, promoting the release or transfer of lithium ions, thereby reducing the decomposition voltage of lithium-containing compounds.

[0057] Nickel can participate in some redox reactions and improve the reversibility of the reactions, which means that during the charging and discharging process, the insertion and extraction of lithium ions are smoother, which is beneficial to reduce the decomposition voltage of the lithium supplement and improve the cycle performance of the battery.

[0058] Cobalt has high catalytic activity and can effectively promote related reactions in the lithium replenishment process and reduce the decomposition voltage. Cobalt can act as a medium for electron transfer and accelerate the transmission and reaction of lithium ions, thereby improving the efficiency of lithium replenishment.

[0059] Manganese can adjust the voltage platform of lithium-supplementing materials and, to a certain extent, improve the energy density of the battery. The decomposition voltage of lithium-containing compounds can be reduced by reasonably controlling the manganese content and valence state.

[0060] Vanadium and its compounds can provide abundant catalytic active sites, which can interact with lithium ions, promote the transport and reaction of lithium ions, and thus reduce the decomposition voltage of lithium-containing compounds.

[0061] Chromium can adjust the crystal structure and lattice parameters of lithium-containing compounds. Appropriate crystal structure and lattice parameters help to improve the transmission rate and storage capacity of lithium ions, thereby improving the performance of lithium supplements and reducing the decomposition voltage.

[0062] According to some embodiments of the present invention, the lithium-containing compound includes at least one of a lithium-containing oxide, a lithium-containing fluoride, and a lithium-containing sulfide.

[0063] Exemplarily, the lithium-containing oxide may include at least one of lithium oxide (Li2O), lithium peroxide (Li2O2), lithium nickel oxide (Li2NiO2), lithium ferrite (Li5FeO4), and lithium cobalt oxide (Li6CoO4).

[0064] The lithium-containing fluoride may include at least one of lithium fluoride (LiF), lithium hexafluorophosphate (LiPF6), and lithium tetrafluoroborate (LiBF4). The lithium-containing sulfide may include lithium sulfide (Li2S).

[0065] According to some embodiments of the present invention, the pore diameter is 10 nm-200 nm.

[0066] The pores of the carbon coating are much larger than the diameter of lithium ions, which allows lithium ions to be exchanged more smoothly between the lithium supplement and the electrolyte during the battery charge and discharge process, helping to improve the battery's rate performance; in addition, the large-pore carbon coating is conducive to the transmission of electrons on the surface of the lithium supplement particles, thereby helping to improve the battery's charge and discharge efficiency and reduce the battery's internal resistance.

[0067] According to some embodiments of the present invention, the lithium supplement material satisfies at least one of the following conditions: V50 The thickness of the carbon coating layer is 1nm-50nm; the mass ratio of the core to the carbon coating layer is 100:(0.5-3).

[0068] Particle size DV50 Also known as the median particle size, it refers to the particle size value corresponding to when the cumulative volume fraction reaches 50% in a particle system when the particles are sorted according to their particle size. In other words, half of the particles in the particle system have a volume smaller than this D V50 The volume of the other half of the particles is larger than D V50 value.

[0069] For example, the particle size D of the lithium supplement material is V50 The particle size D of the lithium supplement material can be 0.5 μm, 1.0 μm, 15. μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm or 5.0 μm. V50 When the particle size is between 0.5μm and 5μm, the lithium supplement material has a smaller particle size, which shortens the diffusion path of lithium ions. During the battery charging and discharging process, lithium ions can be exchanged more quickly between the lithium supplement agent and the electrolyte, which helps to improve the battery's rate performance. In addition, the surface area of ​​lithium supplement materials with small particle size is relatively large, and the contact area between the lithium supplement agent and the electrolyte is also larger, which makes the lithium supplement agent more reactive in the battery and can more fully participate in the electrochemical reaction, thereby improving the lithium supplement efficiency.

[0070] The thickness of the carbon coating layer can be 1nm, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm or 50nm. When the thickness of the carbon coating layer is between 1nm and 50nm, the conductivity of the lithium supplement material can be effectively improved, thereby facilitating charge transfer.

[0071] The mass ratio of the core to the carbon coating layer can be 100:0.5, 100:1, 100:1.5, 100:2, 100:2.5 or 100:3. When the mass ratio of the core to the carbon coating layer is between 100:(0.5-3), it helps to form a carbon coating layer with a thickness between 1nm-50nm.

[0072] According to some embodiments of the present invention, the present invention also provides a method for preparing a lithium-replenishing material, comprising: providing a transition metal compound composite material, the transition metal compound composite material comprising a transition metal compound and a carbon coating layer coating at least a portion of the surface of the transition metal compound, the carbon coating layer having pores; mixing molten metal lithium with the transition metal compound composite material under an inert atmosphere to react, and obtaining the lithium-replenishing material after the reaction is completed.

[0073] The inert atmosphere can be one of nitrogen, helium, neon, and argon. The reaction is carried out under an inert atmosphere because metallic lithium is highly active and easily reacts with water and carbon dioxide in the air.

[0074] The molten lithium metal and the transition metal compound composite material can be mixed by mechanical stirring, ultrasonic vibration, jet mixing, spiral extrusion mixing, etc., and the present invention does not make any specific restrictions.

[0075] The present invention prepares a lithium supplement material by mixing molten metal lithium with a transition metal compound composite material, wherein lithium reacts with the transition metal compound to generate a transition metal and a lithium-containing compound, and the transition metal and the lithium-containing compound can be composited at the nanometer level. When used, the above reaction is reversed to release lithium ions for lithium supplementation.

[0076] According to some embodiments of the present invention, "providing a transition metal compound composite material" includes: mixing a transition metal compound with an organic matter to obtain a mixture; and carbonizing the mixture under an inert atmosphere to obtain the transition metal compound composite material.

[0077] The mixture of the transition metal compound and the organic matter can be mixed by ball milling, mechanical stirring, air flow, ultrasonic mixing, etc., and the present invention does not impose any specific limitation.

[0078] Carbonization refers to the process of separating hydrogen and oxygen from organic matter under high temperature conditions, leaving behind products mainly composed of carbon. During the carbonization process, since organic matter has a certain fluidity when heated, it can be more evenly coated on the surface of the transition metal compound. When the temperature rises to a high temperature, the organic matter undergoes a thermal decomposition reaction to form a carbonized layer with holes.

[0079] In addition, compared to directly mixing and carbonizing transition metal compounds, organic matter, and molten metal lithium, the present invention first carbonizes the transition metal compound and the organic matter to form a transition metal compound composite material, and then reacts with molten metal lithium, which can avoid the metal lithium from reacting with the products (carbon dioxide, water) in the carbonization process of the organic matter in advance and thus failing prematurely.

[0080] According to some embodiments of the present invention, the transition element of the transition metal compound includes at least one of iron, nickel, cobalt, manganese, vanadium and chromium.

[0081] According to some embodiments of the present invention, the transition metal compound includes at least one of cobalt trioxide, cobalt trifluoride, ferroferric tetroxide, ferric trifluoride, and ferrous oxide fluoride.

[0082] Cobalt tetroxide (Co3O4) is a strong oxidant. Lithium, as an active metal, has strong reducing properties. The reaction equation between cobalt tetroxide and lithium is: Co3O4+8Li=3Co+4Li2O, that is, lithium replaces cobalt to generate metallic cobalt and lithium oxide.

[0083] Cobalt trifluoride (CoF3) is also a strong oxidant, and its reaction equation with reducing lithium is: 2CoF3+6Li=2Co+6LiF.

[0084] The reaction equation of ferroferric oxide (Fe3O4) and lithium is: Fe3O4+8Li=3Fe+4Li2O.

[0085] The reaction equation of iron trifluoride (FeF3) and lithium is: 2FeF3+6Li=2Fe+6LiF.

[0086] The reaction equation of ferrous oxide fluoride (FeOF) and lithium is: 2FeOF+4Li=2Fe+2Li2O+2LiF.

[0087] According to some embodiments of the present invention, the organic matter includes at least one of starch, sucrose, glucose, and asphalt.

[0088] Starch has good solubility and dispersibility. When the transition metal compound is mixed with starch by ball milling, the starch can be dissolved and dispersed in water (the solvent added during ball milling), which helps to evenly disperse on the surface of the transition metal compound, thereby forming a uniform carbon coating. In addition, starch has good carbonization properties. During carbonization, the hydrogen and oxygen atoms in the starch escape in the form of small molecules such as water, leaving a carbon skeleton structure, which can effectively coat the surface of the transition metal compound.

[0089] Sucrose has good affinity with transition metal compounds and can be tightly attached to the surface of transition metal compounds. After carbonization, a uniform carbon coating layer can be formed.

[0090] Glucose has a small molecular weight, which makes it have high fluidity and permeability in the ball milling solvent, and can be better coated on the surface of the transition metal compound. In addition, glucose can undergo a carbonization reaction quickly when heated, and the quality of the generated carbon coating is high.

[0091] Asphalt has good adhesion, which means that when mixed with transition metal compounds, it can firmly adhere to the surface of transition metal compounds, which helps to improve the bonding strength of the carbon coating layer. In addition, asphalt itself contains a high proportion of carbon elements, which can provide a large amount of carbon source during the carbonization process.

[0092] According to some embodiments of the present invention, the mass ratio of the transition metal compound to the organic matter is 1:(0.05-0.2).

[0093] Exemplarily, the mass ratio of the transition metal compound to the organic matter can be 1:0.05, 1:0.07, 1:0.1, 1:0.13, 1:0.15, 1:0.18 or 1:0.2. When the mass ratio of the transition metal compound to the organic matter is between 1:(0.05-0.2), the integrity of the coating and the conductivity of the coating layer can be guaranteed. Too little organic content may affect the integrity and conductivity of the carbon coating layer. Too much organic content makes the carbon coating layer too thick, which is easy to affect subsequent chemical reactions. When the carbon content is too high, it will affect the capacity of the lithium supplement material.

[0094] According to some embodiments of the present invention, "carbonizing the mixture to obtain a transition metal compound composite material" includes: heating the mixture from room temperature to a first carbonization temperature, and keeping it warm for 1h-3h; heating the mixture from the first carbonization temperature to a second carbonization temperature, and keeping it warm for 4h-10h.

[0095] The carbonization treatment of the mixture can be carried out in a tube furnace, a muffle furnace, a high-temperature reactor and the like, and the present invention does not impose any specific limitation thereto.

[0096] The present invention adopts a staged carbonization process. At the first carbonization temperature, the organic matter becomes molten and has a certain fluidity. Keeping it warm for 1h-3h can allow the organic matter to fully coat the transition metal compound. At the second carbonization temperature, the organic matter undergoes pyrolysis. Keeping it warm for 4h-10h can allow the organic matter to be fully pyrolyzed and carbonized to form a carbon coating layer with holes.

[0097] According to some embodiments of the present invention, the first carbonization temperature is 300°C-500°C; and / or, the second carbonization temperature is 600°C-1200°C; and / or, the heating rate is 2°C / min-8°C / min.

[0098] Exemplarily, the first carbonization temperature may be 300°C, 320°C, 350°C, 380°C, 400°C, 430°C, 450°C, 470°C or 500°C; the second carbonization temperature may be 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C or 1200°C; and the heating rate may be 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min or 8°C / min.

[0099] According to some embodiments of the present invention, "mixing and reacting molten metallic lithium with a transition metal compound composite material" includes: heating the metallic lithium to 180°C-190°C to obtain molten metallic lithium; adding the transition metal compound composite material to the molten metallic lithium and stirring evenly; and then heating to 200°C-240°C and reacting at a constant temperature for 1h-5h.

[0100] The melting point of metallic lithium is 180.54°C, so molten metallic lithium can be obtained by heating between 180°C and 190°C. The molten metallic lithium can easily come into full contact with the transition metal compound composite material, which helps to increase the degree of reaction.

[0101] Heating to 200°C-240°C facilitates the reaction of lithium with the transition metal compound. Exemplarily, the reaction temperature may be 200°C, 205°C, 210°C, 215°C, 220°C, 225°C, 230°C, 235°C or 240°C.

[0102] According to some embodiments of the present invention, the stirring speed is 5 rpm-30 rpm, and the stirring time is 20 min-40 min.

[0103] When the rotation speed is between 5rpm-30rpm, the fluidity of the metal lithium is enhanced, which can promote the transition metal compound composite material to fully move and diffuse in the molten metal lithium, and help to obtain a uniform reaction system. When the rotation speed is too high, some transition metal compound particles may be drawn into the center of the vortex or thrown near the container wall before they can be fully mixed; when the rotation speed is too low, the fluidity of the molten metal lithium is relatively poor, which is not conducive to the uniform dispersion of the transition metal compound composite material. Exemplarily, the rotation speed can be 5rpm, 10rpm, 15rpm, 20rpm, 25rpm, 30rpm, 35rpm or 40rpm.

[0104] When the stirring time is 20 min-40 min, the transition metal compound composite material can be uniformly dispersed in the molten metal lithium. Exemplarily, the stirring time can be 20 min, 25 min, 30 min, 35 min or 40 min.

[0105] According to some embodiments of the present invention, the present invention further provides a positive electrode plate, the positive electrode plate includes a positive electrode film layer, the positive electrode film layer includes any of the above-mentioned lithium supplement materials or includes a lithium supplement material prepared by any of the above-mentioned preparation methods. The specific arrangement of the lithium supplement material refers to the above-mentioned embodiments. Since the positive electrode plate of the present invention adopts all the technical solutions of all the above-mentioned embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be repeated here one by one.

[0106] According to some embodiments of the present invention, the mass proportion of the lithium supplement material in the positive electrode film layer is 0.5%-5.0%.

[0107] Exemplarily, the mass proportion of the lithium supplement material in the positive electrode film layer may be 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5% or 5.0%.

[0108] Typically, the positive electrode film layer includes a positive electrode active material, and the positive electrode active material can be a positive electrode active material known in the field of lithium batteries. In some embodiments, the positive electrode active material may include lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2), lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and at least one of a composite material of lithium iron manganese phosphate and carbon.

[0109] In some embodiments, the positive electrode film layer may also optionally include a binder. Exemplarily, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0110] In some embodiments, the positive electrode film layer may further optionally include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0111] According to some embodiments of the present invention, the present invention further provides a lithium-ion battery, comprising the above-mentioned positive electrode plate. The lithium-ion battery is a battery cell, a battery module or a battery pack.

[0112] The following is an explanation through specific embodiments.

[0113] Example 1

[0114] [Lithium Supplement Materials]

[0115] Co3O4 and glucose were mixed in a mass ratio of 1:0.15 and ball-milled for 2 hours to obtain a mixture; the mixture was placed in a tubular furnace, N2 was introduced for protection, the temperature was increased to 400°C at a rate of 5°C / min, and the temperature was kept for 2 hours, then the temperature was increased to 800°C at a rate of 5°C / min, and the temperature was kept for 6 hours. After cooling and crushing, a transition metal compound composite material was obtained.

[0116] In an argon atmosphere, the metallic lithium was heated to 185°C, and after the metallic lithium was completely melted, the transition metal compound composite material was added to the molten lithium, stirred at a speed of 10 rpm for 30 min, and then the temperature was raised to 230°C for reaction for 3 h, and then cooled and crushed to obtain a particle size D V50 It is a lithium-supplementing material with a thickness of 4μm.

[0117] [Positive electrode sheet 1]

[0118] The lithium supplement material, conductive carbon black and polyvinylidene fluoride are mixed in a mass ratio of 95:2:3, and a solvent N-methylpyrrolidone (NMP) is added to form a slurry with a solid content of 60%. The slurry is evenly coated on both sides of the aluminum foil, and the positive electrode sheet is obtained after drying, rolling and cutting.

[0119] [Positive electrode sheet 2]

[0120] Lithium iron phosphate (LFP), conductive carbon black, polyvinylidene fluoride, and lithium supplement material are mixed in a mass ratio of 95:2:2:1, and a solvent N-methylpyrrolidone (NMP) is added to form a positive electrode slurry, and the solid content of the positive electrode material is 60%. The positive electrode slurry is evenly coated on both sides of the aluminum foil, and the positive electrode sheet is obtained after drying, rolling, and cutting.

[0121] [Negative electrode]

[0122] Graphite, conductive carbon black, carboxymethyl cellulose and styrene-butadiene rubber are mixed in a mass ratio of 95:1.5:1.5:2, and deionized water is added as a solvent to form a negative electrode slurry, wherein the solid content of the negative electrode slurry is 50%. The negative electrode slurry is evenly coated on both sides of the copper foil, and the negative electrode sheet is obtained after drying, rolling and cutting.

[0123] [Isolation film]

[0124] The diaphragm is made of polypropylene (PP) and has a thickness of 20 μm.

[0125] [Electrolyte]

[0126] The lithium salt of the electrolyte is LiPF6 with a concentration of 1.0M, and the electrolyte solvent is a mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of 1:1:1.

[0127] [Assembly]

[0128] In a glove box, the positive electrode sheet 1, the metal lithium sheet and the diaphragm are stacked in a single layer (one positive electrode sheet 1, one metal lithium sheet and one diaphragm are stacked), the electrolyte is added dropwise, and the battery is packaged into a button cell.

[0129] The positive electrode sheet 2, the negative electrode sheet and the separator are made into a battery cell by Z-shaped stacking, the positive and negative electrode tabs are located on the same side of the battery cell, and the outermost circle of the stacked core adopts a structure that the negative electrode sheets on the upper and lower sides of the stacked core are terminated. Then, the lithium-ion battery is obtained by welding, packaging, liquid injection, formation, exhaust, secondary sealing and capacity separation.

[0130] Example 2

[0131] The difference from Example 1 is that the reaction temperature of the metallic lithium and the transition metal compound in this example is 240° C., and the rest is the same as Example 1.

[0132] Example 3

[0133] The difference from Example 1 is that the reaction temperature of the metallic lithium and the transition metal compound in this example is 200° C., and the rest is the same as Example 1.

[0134] Example 4

[0135] Different from Example 1, the mass ratio of Co3O4 to glucose in this example is 1:0.2, and the rest is the same as Example 1.

[0136] Example 5

[0137] The difference from Example 1 is that the mass ratio of Co3O4 to glucose in this example is 1:0.05, and the rest is the same as Example 1.

[0138] Example 6

[0139] The difference from Example 1 is that the transition metal compound in this example is CoF3, and the rest is the same as Example 1.

[0140] Example 7

[0141] The difference from Example 1 is that the transition metal compound in this example is Fe3O4, and the rest is the same as Example 1.

[0142] Example 8

[0143] The difference from Example 1 is that the transition metal compound in this example is FeF3, and the rest is the same as Example 1.

[0144] Example 9

[0145] The difference from Example 1 is that the transition metal compound in this example is FeOF, and the rest is the same as Example 1. The XRD pattern of the prepared lithium supplement material is as follows: Figure 1 As shown, it can be seen that the lithium supplement material includes diffraction peaks of each single component. It should be noted that since the carbon in the carbon coating layer is amorphous carbon, there is no obvious diffraction peak in the carbon-loaded XRD diagram.

[0146] Comparative Example 1

[0147] The metal Co powder and Li2O are mixed in a molar ratio of 3:4, and the mixture is ball-milled 12 to obtain a lithium supplement material. The rest is the same as in Example 1.

[0148] Comparative Example 2

[0149] The metal Fe powder was mixed with Li2O and LiF in a molar ratio of 4:4:3, and the mixture was ball-milled for 12 hours to obtain a lithium supplement material. The rest was the same as in Example 1.

[0150] Performance Testing

[0151] Charging capacity of lithium supplement material: Continuously charge the button battery at a current of 0.1C to 4.2V to obtain the charging capacity. The charging capacity divided by the weight of the lithium supplement material is the charging capacity of the lithium supplement material.

[0152] Positive electrode gram capacity: The lithium-ion battery is continuously charged at a current of 0.5C to 3.65V, then charged at a constant voltage of 3.65V until the current drops to 0.05C, and then discharged at a current of 0.5C to a voltage of 2.0V to obtain the charging capacity and discharge capacity. The discharge capacity divided by the total weight of the positive electrode active material and the lithium supplement material is the positive electrode gram capacity.

[0153] The first charge and discharge efficiency of the battery: The above discharge capacity divided by the charge capacity is the first charge and discharge efficiency.

[0154] Energy density of battery: The above discharge capacity * average voltage / battery weight is the energy density.

[0155] Test Results

[0156] The test results of Examples 1-9 and Comparative Examples 1-2 are shown in Table 1.

[0157] Table 1 Test results in Examples 1-9 and Comparative Examples 1-2

[0158]

[0159]

[0160] It can be seen from Table 1 that the initial charging capacity of the lithium supplement material in the embodiment of the present application is significantly higher than that in the comparative example, indicating that the lithium supplement material containing a carbon coating layer in the present application can significantly increase the charging capacity of the lithium supplement agent, thereby helping to improve the initial charge and discharge efficiency and energy density of the battery.

[0161] By comparing Examples 1, 4-5, it can be seen that within a given range, with the increase in the amount of organic matter added, the initial charge and discharge capacity of the lithium supplement material, the battery positive electrode gram capacity, the battery initial charge and discharge efficiency and the battery energy density decrease instead, which indicates that a thinner carbon coating layer is more helpful in improving the above performance.

[0162] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.

Claims

1. A lithium supplement material, characterized in that: It comprises a core and a carbon coating layer covering at least a part of the surface of the core; the core comprises a lithium supplement agent, the lithium supplement agent comprises a transition metal element and a lithium-containing compound; the carbon coating layer has holes.

2. The lithium supplement material according to claim 1, characterized in that: The molar ratio of the transition metal element to the lithium-containing compound is 1:(1.3-2).

3. The lithium supplement material according to claim 1 or 2, characterized in that: The transition metal element includes at least one of iron, nickel, cobalt, manganese, vanadium and chromium.

4. The lithium supplement material according to claim 1 or 2, characterized in that: The lithium-containing compound includes at least one of a lithium-containing oxide, a lithium-containing fluoride, and a lithium-containing sulfide.

5. The lithium supplement material according to claim 1, characterized in that: The pores have a diameter of 10 nm to 200 nm.

6. The lithium supplement material according to claim 1, characterized in that: The lithium supplement material meets at least one of the following conditions: The particle size D of the lithium supplement material V50 0.5μm-5μm; The thickness of the carbon coating layer is 1nm-50nm; The mass ratio of the core to the carbon coating layer is 100:(0.5-3).

7. A method for preparing a lithium supplement material, characterized in that: include: A transition metal compound composite material is provided, the transition metal compound composite material comprises a transition metal compound and a carbon coating layer covering at least a portion of the surface of the transition metal compound, the carbon coating layer having pores; Under an inert atmosphere, molten metal lithium is mixed with the transition metal compound composite material for reaction, and a lithium supplement material can be obtained after the reaction is completed.

8. The method for preparing the lithium supplement material according to claim 7, characterized in that: The “providing a transition metal compound composite material” comprises: mixing a transition metal compound with an organic matter to obtain a mixture; The mixture is carbonized under an inert atmosphere to obtain a transition metal compound composite material.

9. The method for preparing the lithium supplement material according to claim 8, characterized in that: The transition element of the transition metal compound includes at least one of iron, nickel, cobalt, manganese, vanadium and chromium.

10. The method for preparing a lithium supplement material according to claim 9, characterized in that: The transition metal compound includes at least one of cobalt trioxide, cobalt trifluoride, ferroferric tetroxide, ferric trifluoride, and ferrous oxide fluoride.

11. The method for preparing a lithium supplement material according to claim 8, characterized in that: The organic matter includes at least one of starch, sucrose, glucose and asphalt.

12. The method for preparing a lithium supplement material according to claim 8, characterized in that: The mass ratio of the transition metal compound to the organic matter is 1:(0.05-0.2).

13. The method for preparing a lithium supplement material according to claim 8, characterized in that: The "carburizing the mixture to obtain a transition metal compound composite material" includes: The mixture is heated from room temperature to a first carbonization temperature and kept at this temperature for 1 h to 3 h; The mixture is heated from the first carbonization temperature to the second carbonization temperature and kept at this temperature for 4 h to 10 h.

14. The method for preparing a lithium supplement material according to claim 13, characterized in that: The first carbonization temperature is 300°C-500°C; and / or, The second carbonization temperature is 600°C-1200°C; and / or, The heating rate is 2°C / min-8°C / min.

15. The method for preparing a lithium supplement material according to any one of claims 7 to 14, characterized in that: The "mixing reaction of molten lithium metal with the transition metal compound composite material" comprises: Heating metallic lithium to 180° C.-190° C. to obtain molten metallic lithium; Adding the transition metal compound composite material into the molten metal lithium and stirring evenly; Then the temperature is raised to 200°C-240°C and the reaction is carried out at a constant temperature for 1h-5h.

16. The method for preparing a lithium supplement material according to claim 15, characterized in that: The stirring speed is 5 rpm-30 rpm, and the stirring time is 20 min-40 min.

17. A positive electrode sheet, comprising a positive electrode film layer, characterized in that: The positive electrode film layer comprises the lithium supplement material according to any one of claims 1 to 6 or comprises the lithium supplement material prepared by the preparation method according to any one of claims 7 to 16.

18. The positive electrode sheet according to claim 17, characterized in that: The mass proportion of the lithium supplement material in the positive electrode film layer is 0.5%-5.0%.

19. A lithium ion battery, characterized in that: Including the positive electrode sheet as described in claim 17 or 18.

Citation Information

Cited By

  • Secondary battery and preparation method thereof, energy storage system and electric equipment

    CN120376792A

  • Lithium-silicon-carbon pre-supplementing negative electrode material as well as preparation method and application thereof

    CN120767316A